Prevalence of hydatidosis in livestocks in Chakwal District of Pakistan - Khan, Aisha; Farooq, Hamza; Simsek, Sami; Gondal, Muhammad Asif; Ahmed, Haroon (Wolters Kluwer Medknow Publications, 2018)
[Abstract Not Available]
Keywords: Hydatidosis; Livestock; Chakwal; Pakistan